مرويات بكر بن حماد التيهرتي من خلال كتاب التمهيد لابن عبد البر - نماذج مختارة - الأطرش, فطيمة; باوة, صفاء (My University, 2022)
"موضوع هذا البحث حول بكر بن حماد التيهرتي ومروياته الواردة في كتاب التمهيد لابن عبد البر، وذلك بمعرفة درجتها صحة وضعفا للخروج بنظرة ولو جزئية المروياته وتوثيق الرواة من من خلال ماجمعناه أحاديث وقسمناها إلى مطلبين: الأحاديث التي أخرجها البخاري، والأحاديث التي لم يخرجها البخاري، درسنا في المطلب الأول خمسة عشر نموذجا وفي المطلب الثاني ستة عشر نموذجا. ""The topic of this research revolves around Bakr Bin Hammad Al Teherti and his narrations contained in the book Al-Tamheed by Ibn Abd Al-Bar, by knowing their degree of validity and weakness in order to come up with a look, even if partial, to his narrators, and to document the narrators through what we collected from the hadiths and divided them into two demands that Al-Bukhari brought out and that Al-Bukhari did not come up with. Fifteen models and the second requirement sixteen models. "
مذكرة ماستر
Keywords: بكر بن حماد، كتاب التمهيد ، ابن عبد البر; Bakr bin Hammad, Le livre de la cabine, Ibn Abd al-Barr